ANALISIS PENJATUHAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENCURIAN DENGAN KEKERASAN (STUDI PUTUSAN NOMOR : 329/PID.B/2021/PN.TJK) - Zulfi Diane Zaini; M Rifky Hendrian Rifky (Magister Hukum Sekolah Pascasarjana Unida, 2023)
The crime of theft with violence is different from ordinary theft, criminal acts of theft with violence such as vandalism, beatings, beatings and others, the threat of punishment is heavier than ordinary theft. The problem in this research is what are the factors that cause the crime of theft with violence? Criminal liability of perpetrators of theft with violence in Decision Number: 329/Pid.B/2021/PN.Tjk? Judge's consideration in the decision of the criminal act of theft with violence in the decision Number: 329/Pid.B/2021/PN.Tjk?. Research method The method used in the preparation of this journal is a normative legal approach and an empirical approach. Based on research on the causative factors are economic factors, malicious intent, the environment, the negligence of the victim. the accountability of the perpetrators is very little and does not provide a deterrent effect to the perpetrators of crimes, so that cases like this can arise again. The judge's consideration by considering the aggravating and mitigating actors in the judicial process. Keywords: Criminal Sanctions; Theft; Violent